Short-acting growth hormone supplementation for bone age and growth rate in children with idiopathic short stature: a meta-analysis - Lianlian Yang; Fan Yang (BMC Pediatrics)
Abstract Objective To explore the effect of short-acting growth hormone (GH) supplementation on bone age and growth rate of children with idiopathic short stature. Methods The authoritative databases such as PubMed, Medline, and Web of Science were extensively searched through the systematic and comprehensive literature retrieval strategy to compile the clinical research data on the treatment of idiopathic short stature with short-acting GH. The study will be strictly screened to ensure that all enrolled research subjects are patients with idiopathic short stature, and the intervention method is defined as short-acting GH replacement therapy, and a reasonable control group is set, such as placebo treatment, to ensure the scientificity and comparability of research results. Outcome index data such as basic characteristics, sample size, follow-up time, and total effective rate of the included studies were extracted. In this study, RevMan 5.3, a professional statistical software tool, was used to systematically perform the meta-analysis process. Weighted average difference (WMD) was calculated as the primary outcome to evaluate the effect of bone age and growth rate, and the WAD in adverse reactions was considered as the secondary outcome. Results Nine studies were included in the study, and 491 patients with idiopathic short stature were included in the study. The results of the meta-analysis showed that there was no significant difference in bone age but a significant difference in growth rate when compared with the control group. Conclusion Short-acting GH supplementation can significantly improve the growth rate of children with idiopathic short stature, but has little effect on bone age.